2000
DOI: 10.1063/1.481042
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ionic mobilities by scattering on electronic density isosurfaces: Application to silicon cluster anions

Abstract: We have developed a new formalism to evaluate the gas-phase mobility of an ion based on elastic scattering on an electronic density isosurface ͑SEDI͒. In this method, the ion is represented by a surface of arbitrary shape defined as a set of points in space where the total electron density assumes a certain value. This value is the only adjustable parameter in the model. Conceptually, this treatment emulates the interaction between a drifting ion and the buffer gas atoms closer than the previously described me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
215
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(245 citation statements)
references
References 88 publications
27
215
3
Order By: Relevance
“…Here the "scattering on electron density isosurface" (SEDI) (Ref. 24) model has been used, where the collision cross section is calculated on the basis of the electron density distribution of each cluster. The SEDI model requires the electron density threshold as adjustable parameter which has to be calibrated against the experimental cross section for one cluster size.…”
Section: A Ion Mobility Spectrometrymentioning
confidence: 99%
“…Here the "scattering on electron density isosurface" (SEDI) (Ref. 24) model has been used, where the collision cross section is calculated on the basis of the electron density distribution of each cluster. The SEDI model requires the electron density threshold as adjustable parameter which has to be calibrated against the experimental cross section for one cluster size.…”
Section: A Ion Mobility Spectrometrymentioning
confidence: 99%
“…First principles quantum mechanical calculations such as the Car-Parrinello method within the generalized gradient approximation (CP-GGA) is successful in predicting the structures of Si clusters up to twenty atoms by Shvartsburg et al (2000). While the CP-GGA method is very accurate in yielding valuable informations about the structure and electronic properties of these clusters, the demand on computational time to optimize medium sized clusters for longer time scales is enormously high.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical investigation is carried out in concert with the experimental threshold photoionization measurements. However, among the investigated species only Si 6 Li 2 , Si 7 Li, Si 10 Li, and Si 11 Li have sufficiently low ionization thresholds allowing experimental determination of their ionization energies. Our ultimate goal is to identify the ground state structure of the clusters and to derive the role of the lithium atoms upon investigation of their growth mechanisms in comparison with the bare silicon clusters.…”
Section: Introductionmentioning
confidence: 99%
“…the center of a Si 8 cube, while the Li − anion is not. 19 Using ab initio molecular dynamics simulations Majumder and Kulshreshtha 20 showed that Be and B atoms are encapsulated in a bicapped tetragonal prism Si 10 , while Li, Na, Mg, and Al prefer to expose on the surface of the clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation